(untitled) (CAHIERS MAGELLANES-NS, 2024)
In a given locality, families living with finance and social status are herein taken into an analysis for locating the living or financing status, though developing a modeling by various approaches. Such status named by FSG in this present study, is symbolized by finance (F), Social (S) and Geography (G) for each and every family. Networking among households gets thereby formed upon finding an interaction between or among families, by FSG, and this network further leads to generation of a modelling, called by FSG modeling in this study. Expressed as theoretical study entirely, it has various usefulnesses to crop up entirety of a locality with regard to F, S and G features or variables, to know one family’s interaction or FSG status (as an effect) upon another family. How a locality is equipped with by present resources (by F,S,G indeed) as available to or how it should be maneuvered to or many such fortunes can be described well by the study’s FSG modelling. It should solve complexity in organizing among families onto their (FSG) distribution agendas or various marketing propositions or insights to bring in alongwith giving scopes of future research to be a doing-for aspect for a country’s mankind.